2010
DOI: 10.1111/j.1755-148x.2010.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Shades of meaning: the pigment‐type switching system as a tool for discovery

Abstract: SummaryThe pigment-type switching system, which controls whether melanocytes produce black ⁄ ⁄ brown eumelanin or yellow ⁄ ⁄ red pheomelanin, is responsible for many familiar coat coloration patterns in both domestic and wild mammals. In conjunction with the accessory proteins attractin and mahogunin ring finger 1, endogenous agonists and antagonists modulate signaling by the melanocortin 1 receptor to determine pigment type.Mutations in pigment-type switching genes can cause a variety of pleiotropic phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 112 publications
0
43
0
Order By: Relevance
“…Thus, carriers of hypomorphic MC1R variants normally display an inefficient or absent tanning response (Healy et al, 2000;Rees, 2004) and a higher risk of melanoma and non-melanoma skin cancer (Box et al, 1997;Box et al, 2001;Duffy et al, 2004;Duffy et al, 2010;Palmer et al, 2000). In keeping with this important biological role, MC1R signaling is highly regulated not only by general mechanisms such as homologous desensitization acting on most if not all GPCRs (Sánchez- Más et al, 2005a), but also by specific mechanisms restricted to the MCR subfamily of GPCRs (Barsh et al, 2000;Pérez-Oliva et al, 2009;Walker and Gunn, 2010). Previous work from our laboratory showed that whereas MC1R signaling to the cAMP pathway is downregulated by GRK2-and GRK6-dependent homologous desensitization (Sánchez- Más et al, 2005a), only GRK6 is involved in agonistpromoted receptor internalization (Sánchez-Laorden et al, 2007).…”
Section: Competitive Association Of Arrb1 and Arrb2 Isoforms With Mc1rmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, carriers of hypomorphic MC1R variants normally display an inefficient or absent tanning response (Healy et al, 2000;Rees, 2004) and a higher risk of melanoma and non-melanoma skin cancer (Box et al, 1997;Box et al, 2001;Duffy et al, 2004;Duffy et al, 2010;Palmer et al, 2000). In keeping with this important biological role, MC1R signaling is highly regulated not only by general mechanisms such as homologous desensitization acting on most if not all GPCRs (Sánchez- Más et al, 2005a), but also by specific mechanisms restricted to the MCR subfamily of GPCRs (Barsh et al, 2000;Pérez-Oliva et al, 2009;Walker and Gunn, 2010). Previous work from our laboratory showed that whereas MC1R signaling to the cAMP pathway is downregulated by GRK2-and GRK6-dependent homologous desensitization (Sánchez- Más et al, 2005a), only GRK6 is involved in agonistpromoted receptor internalization (Sánchez-Laorden et al, 2007).…”
Section: Competitive Association Of Arrb1 and Arrb2 Isoforms With Mc1rmentioning
confidence: 99%
“…Modulation of MC1R activity is responsible for much of the normal variation in mammalian pigmentation. High MC1R activity is associated with eumelanogenesis and darker pigmentation (Ito and Wakamatsu, 2011;Rees, 2004;Robbins et al, 1993), whereas decreased or absent signaling leads to reddish pheomelanogenic pigment production (Beaumont et al, 2007;Duffy et al, 2004;Healy et al, 2000;Healy et al, 2001;Jiménez-Cervantes et al, 2001;Sánchez-Laorden et al, 2006;Walker and Gunn, 2010). Following exposure to ultraviolet radiation (UVR), MC1R also activates DNA repair and survival mechanisms (Böhm et al, 2005;Kadekaro et al, 2005;Kadekaro et al, 2010) as well as antioxidant defences (Kadekaro et al, 2012;Maresca et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the quantity and the ratio of eu-to pheomelanin depend primarily on the activity of tyrosinase and the presence of substrates cysteine and tyrosine in the melanosomes. Two major regulators of melanogenesis, namely the melanocortins and the Agouti protein (ASIP), control the level and activity of the tyrosinase via binding to the melanocortin 1 receptor (MC1R) (Ito and Wakamatsu 2011;Walker and Gunn 2010). Binding of melanocortins, particularly -MSH, to MC1R, induces transcription and activity of eumelanic genes such as MITF, tyrosinase, TRP1 and DCT, and therefore increases the production of black/brown eumelanin.…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism by which MGRN1 may be involved in pigment type switching has remained uncertain, although genetic studies have suggested that it may function downstream of agouti but upstream of, or at the same level as, the MC1R (7). It has also been suggested that MGRN1 may ubiquitinate MC1R to promote its internalization or lysosomal degradation (13), an observation supported by Rouzaud et al (14) who showed that the MC1R protein levels were reduced in cultured melanocytes when stimulated with ASP.…”
mentioning
confidence: 74%